2002
DOI: 10.2337/diabetes.51.4.951
|View full text |Cite
|
Sign up to set email alerts
|

Impaired β-Cell Function, Incretin Effect, and Glucagon Suppression in Patients With Type 1 Diabetes Who Have Normal Fasting Glucose

Abstract: We have recently described a novel phenotype in a group of subjects with type 1 diabetes that is manifested by glucose >11.1 mmol/l 120 min after an oral glucose load, but with normal fasting glucose levels. We now describe the metabolic characteristics of these subjects by comparing parameters of islet hormone secretion and glucose disposal in these subjects to age-matched nondiabetic control subjects. The patients with type 1 diabetes had fasting glucose, insulin, and glucagon values similar to those of cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
71
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(74 citation statements)
references
References 53 publications
2
71
1
Order By: Relevance
“…Previous studies have demonstrated that, in patients with T1D, a paradoxical increase in glucagon occurs in response to an oral glucose challenge (2,8,11). However, these reports have not accounted for the potential effect of prechallenge ambient glycemia and appropriate insulinemia, which could result in differential glucagon responses.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Previous studies have demonstrated that, in patients with T1D, a paradoxical increase in glucagon occurs in response to an oral glucose challenge (2,8,11). However, these reports have not accounted for the potential effect of prechallenge ambient glycemia and appropriate insulinemia, which could result in differential glucagon responses.…”
mentioning
confidence: 80%
“…Indeed, impaired suppression of glucagon after oral ingestion of glucose has been demonstrated in both type 1 diabetes (T1D) and type 2 diabetes (T2D) (2)(3)(4), suggesting that hyperglucagonemia develops in parallel with hypoinsulinemia. Thus, in addition to insulin deficiency, defects in glucagon physiology may be involved in potentiating fasting and postprandial hyperglycemia in diabetes (5).…”
mentioning
confidence: 99%
“…Tissue-specific processing leads to the formation of several similar analogs. GLP-1-(7-36) and GLP-1-(7-37), secreted from enteroglucagon-producing cells (L cells) in the intestinal mucosa during hyperglycemia (15)(16)(17), are potent intestinal insulinotropic hormones that augment insulin secretion (18) and acutely lower glucose levels in rodents and in both type 1 and 2 human diabetic subjects (19)(20)(21)(22). In contrast to these well characterized molecules, GLP-1-(1-37), formed in very small amounts by pancreatic glucagon-producing ␣ cells, has little effect on insulin release (23).…”
Section: Glp-1-(1-37) Induces Insulin Expression In Intestinal Epithementioning
confidence: 99%
“…Whereas type 2 diabetes is clearly characterized by gradual loss of insulin secretion, the insulin deficit in type 1 diabetes is the result of more or less massive and rapid autoimmune destruction of the ␤-cell mass (1,13). However, a recent report indicates that in the early stages of the disease, certain type 1 diabetic patients show some degree of ␤-cell dysfunction, manifested primarily by hyperglycemia after glucose loading due to a defective insulin secretion (17). Interestingly, a similar impairment in insulin secretion has also been observed in the IRS-1 null mice, both in vivo and in vitro (18).…”
Section: Irs-1 Variant Was Transmitted From Heterozygous Parents To Amentioning
confidence: 74%